2021
DOI: 10.1159/000513033
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Plasma Trimethylamine N-Oxide Levels and Renal Dysfunction in Patients with Hypertension

Abstract: <b><i>Introduction:</i></b> Trimethylamine N-oxide (TMAO) is a metabolite produced by gut bacteria. Although increased TMAO levels have been linked to hypertension (HTN) and chronic kidney disease (CKD) with poor prognosis, no clinical studies have directly addressed the relationship between them. In this study, we investigated the relationship between TMAO and renal dysfunction in hypertensive patients. <b><i>Methods:</i></b> We included healthy controls (<i&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(45 reference statements)
0
10
1
1
Order By: Relevance
“…TMA concentration was higher in the liver (437 nM/g) and kidney in the Da Costa study (531 nM/g) than in our study. TMAO concentration in the liver was over 100-fold higher (633 nM/g) than in our study, while TMAO concentration in the kidneys was not provided by Da Costa et al It needs to be stressed that, in contrast to relatively simple and reproducible measurements of TMAO levels across numerous studies [ 4 , 8 , 10 , 14 , 16 , 18 21 , 66 ], the measurements of TMA are much more difficult. There are discrepancies in reported absolute TMA levels across the few available studies [ 11 , 23 , 24 , 33 , 35 , 65 , 67 69 ].…”
Section: Discussioncontrasting
confidence: 81%
“…TMA concentration was higher in the liver (437 nM/g) and kidney in the Da Costa study (531 nM/g) than in our study. TMAO concentration in the liver was over 100-fold higher (633 nM/g) than in our study, while TMAO concentration in the kidneys was not provided by Da Costa et al It needs to be stressed that, in contrast to relatively simple and reproducible measurements of TMAO levels across numerous studies [ 4 , 8 , 10 , 14 , 16 , 18 21 , 66 ], the measurements of TMA are much more difficult. There are discrepancies in reported absolute TMA levels across the few available studies [ 11 , 23 , 24 , 33 , 35 , 65 , 67 69 ].…”
Section: Discussioncontrasting
confidence: 81%
“…Also, recently Zhou et al studied the relationship between circulating plasma TMAO levels and HTN. They found that TMAO levels are higher in patients with HTN than those without HTN [96]. Hsu et al reported that a higher TMA level is associated with high BP load and abnormal 24-h ambulatory BP monitoring profile, along with the reduced abundance of genus Akkermansia [92].…”
Section: Trimethylamine-n-oxidementioning
confidence: 99%
“…studied the relationship between circulating plasma TMAO levels and HTN. They found that TMAO levels are higher in patients with HTN than those without HTN [ 96 ]. Hsu et al .…”
Section: Mechanisms Of Gut Microbiota-mediated Htnmentioning
confidence: 99%
“…Additionally, our result of increased sCD14 levels correlating with TMAO provides further evidence of gut barrier permeability among KF patients. That progression to KF further disturbs the gut flora and further impairs the intestinal barrier allowing for translocation of uraemic toxins into the systemic circulation thus worsening inflammation leading to negative effects and dysfunction in other organs 69 , 70 . Degradation of occludin in cerebral microvessels in a rat model of ischaemic stroke contributed to BBB disruption and resulted in decreased occludin immunostaining in microvessels, which was reflected by the increased occludin levels in the blood 25 .…”
Section: Discussionmentioning
confidence: 99%